2002
DOI: 10.1038/sj.bjc.6600608
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity in survivors of Wilms' tumours in the North of England

Abstract: One aspect of concern for survivors of Wilms' tumour has been the late outcome in terms of renal function. Previous studies have documented low glomerular filtration rate and high blood pressure in some patients. Furthermore, disorders in tubular function (especially urinary concentration defects) have been suggested but not confirmed in small studies. The aim of this study was to determine the prevalence and nature of subclinical and overt glomerular, proximal and distal renal tubular toxicity in a population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Most commonly this is a type of renal-vascular hypertension caused by compression of the renal artery by a large tumor mass. The effects of treatment for Wilms' tumor on blood pressure have also been analyzed by other authors [10,12,14]. In the 2002 study conducted by Bailey et al, [10] increased blood pressure was shown in 2% of the 40 patients during follow-up examinations after treatment for nephroblastoma.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Most commonly this is a type of renal-vascular hypertension caused by compression of the renal artery by a large tumor mass. The effects of treatment for Wilms' tumor on blood pressure have also been analyzed by other authors [10,12,14]. In the 2002 study conducted by Bailey et al, [10] increased blood pressure was shown in 2% of the 40 patients during follow-up examinations after treatment for nephroblastoma.…”
Section: Discussionmentioning
confidence: 94%
“…In the study by Bailey et al [10], microalbuminuria was found in 5% of the patients (n = 2), and in a study by Levitt et al [13] it was noted in 9% of the patients; in neither study did the patients show any other symptoms of renal dysfunction at the same time. In a study carried out by Di Tullio microalbuminuria was noticed in more patients: 35% of all those tested [12].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Some investigators consider post-nephrectomy renal dysfunction as clinically insignificant (19,20). In contrast, other investigators consider this renal dysfunction to be a harbinger of longterm consequences (21,22).…”
Section: The Function Of Solitary Kidney In Wtsmentioning
confidence: 99%